Language Contact, Contamination, Containment, and Shift: Lessons From Multilingual Gwanda South, Zimbabwe - Erasmos Charamba; Omphile Marupi (Journal of Languages and Language Teaching, 2023)
This article seeks to evaluate the level and type of changes in Sesotho as a result of language contact in multilingual Gwanda South, Zimbabwe. It will indicate choices that speech communities have and reasons for specific language preferences. It looks at the multilingual situation in Gwanda South and the language choices that the community is free or forced to make. It seeks to indicate how language contact could result in language shifts in supposed multilingual communities that could be affected by other languages appearing and being used for essential social, political, religious, and administrative purposes. Survey data reveals that Gwanda South has the following languages: Sesotho, Ndebele, Chi-Jahunda, Venda, and English. Sesotho is the home language while Ndebele has come through administrators and its being the original national language for Matabeleland South. Chi-Jahunda is a primary/ indigenous variety for Gwanda South. Attention is centered on the apparent move from the home language to other varieties that have moved into the district over time. The main worry is the apparent demise of the home language due to both internal and external forces. While there might be a high level of retention of the language in the home domain, the use of languages that are spoken by the few combined with English as the official language tends to interfere with the retention and continued use of Sesotho. This suggests that language contact leads to a shift influenced by a speaker’s inability to preserve their mother language by switching to dominant languages as mediums at home and school once such languages have been learned and mastered.